2011
DOI: 10.3168/jds.2010-3719
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Genomic selection using a multi-breed, across-country reference population

Abstract: Three breeds (Fleckvieh, Holstein, and Jersey) were included in a reference population, separately and together, to assess the accuracy of prediction of genomic breeding values in single-breed validation populations. The accuracy of genomic selection was defined as the correlation between estimated breeding values, calculated using phenotypic data, and genomic breeding values. The Holstein and Jersey populations were from Australia, whereas the Fleckvieh population (dual-purpose Simmental) was from Austria and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 12 publications
10
79
0
Order By: Relevance
“…A number of studies (Hayes et al, 2009;Pryce et al, 2011;Erbe et al, 2012;Olson et al, 2012) report on the effect of (Pryce et al, 2011). Generally, no improvements are observed in the accuracies of GEBV for HF when Jersey animals are added to the reference population, and for Jersey animal results are similar or worse when using 54 k data and GBLUP methods (Hayes et al, 2009;Erbe et al, 2012).…”
Section: Genomic Prediction In Small Populationsmentioning
confidence: 99%
“…A number of studies (Hayes et al, 2009;Pryce et al, 2011;Erbe et al, 2012;Olson et al, 2012) report on the effect of (Pryce et al, 2011). Generally, no improvements are observed in the accuracies of GEBV for HF when Jersey animals are added to the reference population, and for Jersey animal results are similar or worse when using 54 k data and GBLUP methods (Hayes et al, 2009;Erbe et al, 2012).…”
Section: Genomic Prediction In Small Populationsmentioning
confidence: 99%
“…One way to increase the reference population size for selection would be to use a breed with more genotyped individuals in the reference population for a breed with fewer candidates. It was found that for Holsteins and Jerseys, one breed could not be directly used as the sole reference population for selection in the other breed using the 50k marker panel, but results showed more promise when both breeds were combined into a common population (Pryce et al, 2011). For genomic selection to be effective, markers and QTL need to be in the same linkage phase across the populations, and must be consistent from the reference population to the validation population.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, they generally have lower population sizes and may be spread over several geographic regions. This has limited the size of reference populations and the resulting predictions are less accurate (Pryce et al 2011b). In addition, some of these breeds have higher effective population sizes than do Holsteins (e.g.…”
Section: Implementation In Other Dairy Cattle Breedsmentioning
confidence: 99%